ANALISIS PENGARUH BEBERAPA FAKTOR SOSIAL EKONOMI TERHADAP KONSUMSI TELUR AYAM RAS PADA TINGKAT RUMAH TANGGA DI KOTA SURAKARTA - Cahyaningrum, Kurnia; Sarosa, Bambang (Universitas Sebelas Maret, 2004)
This research is aimed to find out the influence of some social economic factors to the chicken eggs consumption on household level in Surakarta City and also to know which/actor give the biggest influence. It had been done on April 2004. it was using the descriptive methods, whether the analysis was double linear regression_ with classic assumption. The primary data was taken by observing, interviewing, ang also noting. The research area chosen purposively and the samples taken in the proportional stratified random sampling method. . The result shows that the examine variables is significantly influence the variation of the chi ken eggs consumption, because F counted is bigger than F table in 95 %faith level. From the determination coefficients (R . .), known that the donation of the number of family, household income, the price of chiken eggs, the price of village cluster chisken eggs, the price of duck eggs and the price of fried oil were 77, 9% and the rest was influence by another variables outside the model\'. From the t test, known that the number of family, household income, the price of chicken eggs and the price of duck eggs were influent significantly in 95% faith. And from the partial regression coefficients shows that the number of family has the biggest influence to the chicken eggs consumption household in Surakarta City. Based on the price elasticity score (-8,263), chicken eggs consumption that the elastic demand. Cross price elasticity suggested a related subtitution between chicken eggs and duck eggs. And from the income elasticity, chicken eggs were normal goods.